(3GdehGRfI GdYGeI ddOhdI hGdSjGSGJ GdGbJUGOjI (B:s (3efGgL, JLOjO h GJLGgGJ eYGUQI (B/s - (3bOj, YHO GdeLjOs ((3JdeSGf(B: s (3GdfTQ GdLGeYj GdLOjO(B, s, 2022)
(3GdehGRfI GdYGeI ddOhdI (B: (3GdeHGOF h GdGYOGO h GdJfajP, GdehGRfI GdYGeI h fTGWGJ GdOhdI , GdGWGQ GdbGfhfj ddehGRfI GdYGeI , ehGRfI GdHfhO , ehGRfI GdHQGeL h GdCOGA , ehGRfI GdJNWjW h GdHQeLI , GdehGRfI GdUaQjI, GdehGRfI GdJYGbOjI , ehGRfI GdLeGYGJ GdeMdjI , JQTjO GdfabGJ GdYGeI h GdGfVHGW GdeGdj, TadajI GdehGRfI GdYGeI , YLR GdehGRfI GdYGeI h CSGdjH GdYdGL , GdGSJOGeI GdehGRfjI(B((3GdeGdjI(B)(3, GdUfGOjb GdSjGOjIh GdehGRfI GdYGeI , COGA GdehGRfI GdYGeI h eDTQGJ bjGSg(B.s
(3eQGLYs
Keywords: (3GdejRGfjIs; (3GdfabGJ GdYGeIs